Cotula sericea resolved as the correct name for the mysterious C. fallax (Asteraceae: Anthemidae), with new synonyms and the new combination cotula discolor - Manning, J.; Mucina, Laco; Magee, A. (Elsevier, 2013)
Cotula sericea L.f. was based on an unlocalised collection from the southwestern Cape of a species with conspicuously petiolate, palmately bipinnatisect leaves and long, leafless scapes with discoid capitula subtended by glabrous, uninerved involucral bracts. It has, however, been historically misapplied to plants from the southern and southeastern South African coast with the leaves extending onto the base of the apically inflated peduncle and with shortly radiate capitula and ovate, ±. trinerved bracts. The nomenclatural and taxonomic history of the species is clarified and a lectoype is designated. True C. sericea is a high altitude, local endemic restricted to a few mountains in the Cold Bokkeveld of Western Cape, and we provide a full description and illustration based on wild-collected material. We conclude that it is an older name for the mysterious Cotula fallax D.J.N.Hind, recently described from cultivated material of unknown but possibly South African origin, and which we accordingly place in synonomy. The name Cenia discolor DC. is available for the heterogamous coastal taxon and we make the new combination Cotula discolor (DC.) J.C. Manning & Mucina for it in Cotula. Finally, we conclude that the poorly known Cotula mariae Bremer & Humphries from Cape Recief, Port Elizabeth, is an extreme maritime form of Cotula discolor and reduce it to synonomy.